A Nitbit Citation of the Contributions of Sheikh Abdullahi Fodiyo in the Public Health of The 19th Century West Africa and Beyond: A Case Study of "Kitaabu Niyyati Fil' A'amaliddunyawiyyati Wal'ddiniyyati" - Gidadawa, Fatima Abubakar; Bashar, Tambari Abbas; Sarkingobir, Yusuf (International Journal of Education, Culture, and Society, 2023)
Nowadays, invariably health improvement, health education, health benefits are attached to religiosity as confirmed by inexhaustible literatures. This paper reviewed some of the contributions of Sheikh Abdullahi Fodiyo in the public health of 19th century West African Sokoto Caliphate and afterwards in his famous book called "KITAABU NIYYATI FIL' A'AMALIDDUNYAWIYYATI WAL'DDINIYYATI" (A book of intentions in the issues of world and religion). In the examined book, he stressed the importance of cleanliness, ablution, prayer, work/ employment/ wealth, agriculture, and meat production in the development and sustainability of society, let alone the Muslim ummah. He warned against unemployment, lack of personal hygiene, poor production and handling of food/ meat among others. Certainly, the book exhorts benefits to public health especially in Islamic societies. There is need to use religion as health education, and health promotion tool especially in religious societies for better health and interventions.